2006
DOI: 10.1021/jf052890d
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic and Antioxidant Effects of Extracts from Pleurotus citrinopileatus

Abstract: Pleurotus citrinopileatus is a popular edible mushroom which is physiologically active in both humans and animals. In the study we investigate the effects of this mushroom on hyperlipidemic hamster rats. Four dietary forms of the mushroom were created as follows. The powdered dry fruiting body, hot-water extract, and two kinds of elutes were obtained, from ethyl acetate extract and methanol extract, respectively, in different mixed proportion solvents over silica gel column chromatography (referred to as EAE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 45 publications
3
64
0
1
Order By: Relevance
“…As with other studies on mushroom extracts 26,27,32 , the reducing power abilities of mushroom extracts increased with concentration (Fig. 2).…”
Section: Ferric Reducing-antioxidant Powersupporting
confidence: 87%
“…As with other studies on mushroom extracts 26,27,32 , the reducing power abilities of mushroom extracts increased with concentration (Fig. 2).…”
Section: Ferric Reducing-antioxidant Powersupporting
confidence: 87%
“…This sterol is becoming an important research topic because its content is usually associated with structural and growing fungal characteristics, such as maturation, hyphal formation and sporulation (Villares et al 2012), being also dependent on the fungal species (Phillips et al 2011). From the bioactivity point of view, ergosterol has great importance since it can be converted into vitamin D 2 after photolysis and thermal rearrangement (Villares et al 2012), and was reported as having health-promoting properties such as antioxidant (Shao et al 2010), anti-inflammatory (Kuo et al 2011) and antihyperlipidemic (Hu et al 2006) activities, being also involved in the activated expression of specific defense genes (Lochman and Mikes 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the health-promoting properties of ergosterol, including the 13 antioxidant (Shao et al 2010), anti-inflammatory (Kuo et al 2011) antihyperlipidemic (Hu et al 2006), genetic expression control (Lochman and Mikes 2005) and antitumoral activities (Takaku et al 2001;Yazawa et al 2000), are closely related to the uptake doses. Furthermore, it will be important to understand how its concentration varies during the main fungi development stages.…”
mentioning
confidence: 99%
“…There is a need for a drug that may control both hypercholestrolaemia and hypertriglyceridaemia. Hence the nutritional inhibition or reduction of hypercholestrolaemic conditions is considered to be an important therapeutic approach and efforts have been made to identify medicinal plants with these functions 7,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%